To complete the square for the quadratic equation \( y = x^2 - 16x + 14 \), we can follow these steps:
-
Start with the equation: \[ y = x^2 - 16x + 14 \]
-
Focus on the \( x^2 - 16x \) part:
- To complete the square, take half of the coefficient of \( x \) (which is -16), square it, and then add and subtract that square inside the equation.
- Half of -16 is -8, and squaring that gives \( 64 \).
-
Rewrite the equation: \[ y = (x^2 - 16x + 64) - 64 + 14 \] \[ y = (x - 8)^2 - 50 \]
Now the equation is in vertex form \( y = (x - h)^2 + k \), where \( (h, k) \) is the vertex.
- Identify \( h \) and \( k \):
- Here \( h = 8 \) and \( k = -50 \).
Thus, the vertex is \( (8, -50) \).
The correct answer is D: (8, -50).